A Macroeconomic Framework without Interest: IS–LM Dynamics in Islamic Economics - Abdul Mujib; Rahmatullah Rahmatullah; Kaipal Wahyudi; Fahmi Makraja; M. Fijar Ishlahul Ummah (Universitas Islam Sultan Agung, 2026)
Purpose - The reliance on interest rates in conventional macroeconomic models, particularly within the IS-LM framework, creates a fundamental incompatibility with Islamic economics, where interest (ribā) is strictly prohibited. This incompatibility gives rise to a theoretical gap in the development of macroeconomic models that are aligned with Islamic law (sharīʿah) principles while maintaining analytical robustness. This study aims to reformulate the IS-LM model into a sharīʿah-compliant macroeconomic framework by eliminating the interest rate variable. In its place, a profit-sharing rate (π) is introduced as the primary determinant of investment and money demand.Methodology/approach - To achieve this objective, the research adopts a theoretical and mathematical approach, reconstructing both the IS and LM curves. The proposed model integrates Islamic fiscal instruments, such as zakah, alongside interest-free monetary instruments, including Islamic bonds (sukuk). Concurrently, behavioural functions are modified to reflect incentives oriented toward the real sector, in line with the values of Islamic economics.Findings – This study demonstrate that macroeconomic equilibrium can be achieved without reliance on interest rates. Instead, equilibrium is driven by profitability mechanisms and asset-backed financing structures, which ensure a closer linkage between the financial sector and the real economy. The significance of these findings lies in providing an alternative analytical framework for policymakers, particularly in Muslim-majority countries. Such a framework enables the design of effective fiscal and monetary policies that are also consistent with sharīʿah principles.Conclusion - The proposed IS-π/LM model offers a viable and coherent macroeconomic framework. It replaces interest-based mechanisms with profit-sharing arrangements, thereby supporting the development of a distinct, ethical, and productivity-oriented Islamic economic paradigm. Moreover, the model contributes to the theoretical advancement of Islamic macroeconomics by offering a structured and operational alternative to conventional interest-based systems.